2019
DOI: 10.1002/1873-3468.13514
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid variants of the HybB membrane subunit of Escherichia coli [NiFe]‐hydrogenase‐2 support a role in proton transfer

Abstract: [NiFe]‐hydrogenase (Hyd) 2 of Escherichia coli has been proposed to generate proton motive force during H2‐oxidation, which it is dependent on if cells are incubated anaerobically with glycerol to drive reverse H2‐production. The integral membrane subunit HybB is required for proton transfer (PT) by Hyd‐2 but has no cofactor. To provide evidence for PT by HybB, we analyzed the roles of conserved amino acid residues in a predicted proton channel. Exchange of conserved residues identified residues Y99, E133, H18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…It can be further observed that the effect of CCCP addition is not immediate, but H 2 production rates shift rather gradually. For the direct dependence of an activity on pmf, we have previously observed immediate and complete effects of CCCP addition on the activity [2], suggesting an indirect effect of CCCP occurs here. Notably, the addition of other protonophores like 2,4-dinitrophenol (DNP) up to 1 mM had no effect on the H 2 production activity of the cells, similar to what was observed before at lower concentrations [8].…”
Section: Cccp Inhibits H 2 Production To Different Degrees Depending ...supporting
confidence: 66%
See 2 more Smart Citations
“…It can be further observed that the effect of CCCP addition is not immediate, but H 2 production rates shift rather gradually. For the direct dependence of an activity on pmf, we have previously observed immediate and complete effects of CCCP addition on the activity [2], suggesting an indirect effect of CCCP occurs here. Notably, the addition of other protonophores like 2,4-dinitrophenol (DNP) up to 1 mM had no effect on the H 2 production activity of the cells, similar to what was observed before at lower concentrations [8].…”
Section: Cccp Inhibits H 2 Production To Different Degrees Depending ...supporting
confidence: 66%
“…CCCP enhances Hyd-2 activity by removing the back-pressure of the pmf on the enzyme. When assayed directly, the effect is not very prominent because the enzyme works at its catalytic optimum, but in variants that exhibit difficulties in transferring electrons across the membrane, the effect is more pronounced [2]. Electrons from Hyd-2 are concomitantly channeled into the quinone pool for reduction of electron acceptors like fumarate, which can be internally produced during mixed-acid fermentation when glucose is provided to the cells [28].…”
Section: Hyd-1 Confers Resistance and Hyd-2 Sensitivity Of H 2 Produc...mentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme primarily sustains anaerobic hydrogenotrophic growth of E. coli using fumarate as an electron acceptor (77,214,219,227). It is thought that this hydrogenase can also generate PMF by coupling electron transfer to vectorial proton translocation via its transmembrane subunit (213,214,228). On some fermentable substrates, this complex can also act in reverse as a PMF-driven quinol-dependent proton reductase in a process thought to counterbalance an overreduced redox state of the quinone pool (206,214).…”
Section: Enterobacterialesmentioning
confidence: 99%
“…The presence of an ion-conducting pathway in HybB is also supported by the observations that replacement of Arg89 HybB , Tyr99 HybB , Glu148 HybB and His184 HybB in E. coli HybB (Nside half-channel TMH 5-8) significantly decreased hydrogen oxidation (Lubek et al, 2019). Addition of a protonophore increases hydrogen oxidation in these mutated strains (Lubek et al, 2019), showing that ion translocation and catalytic activity are coupled.…”
Section: Ion Translocation Pathwaysmentioning
confidence: 67%